Streptococcus mutans Lacking sufCDSUB Is Viable, but Displays Major Defects in Growth, Stress Tolerance Responses and Biofilm Formation - Ellepola, Kassapa; Huang, Xiaochang; Riley, Ryan P.; Bitoun, Jacob P.; Wen, Zezhang Tom (Frontiers in Microbiology, 2021)
Streptococcus mutans appears to possess a sole iron-sulfur (Fe-S) cluster biosynthesis system encoded by the sufCDSUB cluster. This study was designed to examine the role of sufCDSUB in S. mutans physiology. Allelic exchange mutants deficient of the whole sufCDSUB cluster and in individual genes were constructed. Compared to the wild-type, UA159, the sufCDSUB¬-deficient mutant, ∆suf::kanr, had a significantly reduced growth rate, especially in medium with the absence of isoleucine, leucine or glutamate/glutamine, amino acids that require Fe-S clusters for biosynthesis and when grown with medium adjusted to pH 6.0 and under oxidative and nitrosative stress conditions. Relative to UA159, ∆suf::kanr had major defects in stress tolerance responses with reduced survival rate of >2-logs following incubation at low pH environment or after hydrogen peroxide challenge. When compared to UA159, ∆suf::kanr tended to form aggregates in broth medium and accumulated significantly less biofilm. As shown by luciferase reporter fusion assays, the expression of sufCDSUB was elevated by >5.4-fold when the reporter strain was transferred from iron sufficient medium to iron-limiting medium. Oxidative stress induced by methyl viologen increased sufCDSUB expression by >2-fold, and incubation in a low pH environment led to reduction of sufCDSUB expression by >7-fold. These results suggest that lacking of SufCDSUB in S. mutans causes major defects in various cellular processes of the deficient mutant, including growth, stress tolerance responses and biofilm formation. In addition, the viability of the deficient mutant also suggests that SUF, the sole Fe-S cluster machinery identified is non-essential in S. mutans, which is not known in any other bacterium lacking the NIF and/or ISC system. However, how the bacterium compensates the Fe-S deficiency and if any novel Fe-S assembly systems exist in this bacterium await further investigation.